Ayla Kutlu and Bejan Matur: Two Pioneering Mediterranean Turkish Women Writers - Micallef, Roberta (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2025)
In this article, I examine Ayla Kutlu’s “Sen de Gitme Triyandafilis” (Please Don’t Go: Triyandafilis), a novella included in the collection of the same title and selected poems by Bejan Matur to gain a deeper understanding of what the label ‘Mediterranean’ signifies regarding the authors and their work, I apply tools afforded by Area Studies, and Comparative Literature to argue that these two authors provide readers with a deeper understanding of Mediterranean identities and literature. Shaped by the Mediterranean region, Matur and Kutlu write about overlapping themes from different vantage points and think about the past in distinct ways. Kutlu, a generation older and a proud daughter of the Turkish nation-state although of Chechen origins and Matur, a local Kurdish woman, are separated by age, ethnicity, religion, and mother tongue; however, their texts are united in their exploration of women’s experiences of the Mediterranean. Examining the texts in their source language with conceptual frames and close reading allows the reader to see that despite Kutlu and Matur’s vastly different relationships to the Turkish state, both authors yearn for the days when diverse communities could live side by side on the Turkish Mediterranean coast, in a cosmopolitan milieu.